Signature dish: Triangulation from data signatures to examine the role of security in falling crime - Graham Farrell; Andromachi Tseloni; Nick Tilley (Methodological Innovations, 2016)
This article describes realist evaluation research combining data signatures and theories of causal mechanism as a means of shedding light on why crime has declined in recent years. A data signature is an empirical indicator of how or why something has occurred. The use of multiple signatures – a ‘dish’ – from different angles and contexts can, if they point in the same direction, result in a form of triangulation that reduces the chance of interpretive error. The signatures identified strongly suggest that more and better security played a key role in the global ‘crime drop’, and in so doing, they rebut rival hypotheses.